Taxation of fuel and vehicles when emissions are constrained - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2021)
A tax on fuel combined with tax exemptions or subsidies for fuel-efficient vehicles is implemented in many countries to fulfill the Paris agreement and to curb mileage-related externalities from road traffic. The present study shows that a tax on fuel should be combined with heavier taxation of lowand zero emission vehicles to curb mileage-related externalities and to fulfill emission targets within the transport sector. The emission target is fulfilled by adjusting the CO2-tax component on fuel. The road user charge on fuel is designed to curb mileage-related externalities. The heavier tax on lowand zero emission vehicles prevent motorists from avoiding the road user charge on fuel by purchasing low- and zero emission vehicles.
Keywords: H2; H21; H23; Q58; R48; 330; Transportation; optimal taxation; environmental taxation; global warming